AB1095 THE GENETIC CHAMELEON IN RHEUMATOLOGY'S BACK GARDEN: A 2-CASE PRESENTATION. (June 2019) - Moldovan, Anca; Felea, Ioana; Damian, Laura; Rancea, Raluca; Bene, Liliana; Boloșiu, Calin; Rednic, Simona
Abstract : Background: Adult Refsum disease is an autosomal recessive disorder, in which phytanic acid cannot be metabolized and it accumulates in plasma and lipid-containing tissues (1). Although its common clinical features are known, patients are displaying symptoms that can mimic an autoimmune pathology, making this disease a diagnostic dilemma. Objectives: To highlight the overlap between the clinical and serological features of adult Refsum disease with those of a connective tissue disease, in order to achieve the correct diagnosis and make appropriate therapeutic decisions. Methods: Clinical and laboratory data were evaluated for 2 patients with adult Refsum disease in a rheumatology tertiary department. The data was retrieved from patients' files. Results: Both patients were females in their 50s with undiagnosed adult Refsum disease. A medical history revealed that both reported progressive nyctalopia, anosmia, ageusia, peripheral vision loss. In addition to these clinical features one of them reported muscle weakness, weight loss and fatigue, displaying periorbital oedema, heliotrope rash, periungual capillary changes. Her muscular enzymes were elevated (creatin-kinase was 3 times elevated and lactat dehydrogenase was 9 times above normal range), along with C-reactive protein (CRP = 2.4mg/dl). Due to clinical features, increased serum enzymes and a recently diagnosed myocarditis, a high suspicion of dermatomyositis was raised, but was disregarded after extensive investigations (immunology tests, muscular biopsy). The other patient had, in addition, sicca features (dry mouth, eyes, skin) with a Schirmer test of 4mm and an elevated CRP (3.23mg/dl). She was referred to the rheumatology department with a high suspicion of Sjogren's syndrome. Immunology and minor salivary gland biopsy were negative. Interestingly, physical examination showed bilateral brachymetacarpia and brachymetatarsia in both patients, suggesting pseudopseudohypoparathyroidism but, after investigations, the diagnosis was excluded. Both patients underwent ophthalmological examination to further investigate progressive nyctalopia and peripheral vision loss. Specific changes for pigmentary retinopathy were described, which, together with the above neurological changes and skeletal deformities, were highly suggestive of adult Refsum disease (2). Plasma phytanic acid was 41 and 42 times above normal range respectively, confirming the diagnosis. After dietary restrictions which excluded phytanic acid containing foods, there was an improvement concerning both clinical and serological manifestations. All connective tissue disease relating symptoms, slowly and gradually started to subside. Muscular enzymes and CRP values returned within normal range (3). Conclusion: High levels of phytanic acid have triggered a series of uncommon symptoms and serological changes resembling a connective tissue disease, making the diagnosis of adult Refusm disease a very tangled, costly and lengthy process. Although this disease affects many body systems, a case of myositis or sicca syndrome hasn't yet been acknowledged in relation to this condition. References: [1] Wierzbicki A.S., Lloyd M.D, et al. Refsum's disease: a peroxisomal disorder affecting phytanic acid alpha-oxidation. Journal of Neurochemistry, 2002, 80, 727-735. [2] Gibberd F.B., et al. Heredopathia atactica polyneuritiformis: Refsum's disease. Acta Neurol Scand 1985;72:1-17. [3] Baldwin E., Gibberd FB, et al. The effectiveness of long term dietary therapy in the treatment of adult Refsum disease. J Neurol Neurosurg Psychiatry 2010;81:954-957. Disclosure of Interests: None declared